Photocatalytic Hydrogen Production by Boron Modified TiO2/Carbon Nitride Heterojunctions. Issue 24 (26th November 2019) - Christoforidis, Konstantinos C.; Montini, Tiziano; Fittipaldi, Maria; Jaén, Juan José Delgado; Fornasiero, Paolo
Abstract: Boron‐doped anatase TiO2 particles were effectively coupled with carbon nitride (CN) forming nanocomposites. The materials were fully characterized by DR‐UV‐Vis, N2 adsorption‐desorption isotherms, XRD, Raman, FTIR, TGA, XPS, TEM, electron energy loss spectroscopy, photoluminescence, and electron paramagnetic spectroscopy (EPR) spectroscopy. The developed heterojunctions were applied as photocatalysts for hydrogen (H2 ) evolution by the photoreforming process of ethanol under solar irradiation, using minimal amount of Pt nanoparticles (0.1 wt. %) as co‐catalyst. The effects of boron addition and CN content were evaluated and optimized nanocomposite presented 85 % increase in H2 evolution compared with the pure anatase TiO2 catalyst. The observed higher H2 evolution rates were ascribed to improvements in charge formation and separation efficiency due to the B‐dopant and the presence of CN. Abstract : Photocatalysis : Photocatalytic hydrogen production is significantly improved via doping TiO2 with boron and coupling with carbon nitride.